How does corporate management affect green innovation via business environmental strategies? - Javeed, Sohail Ahmad; Zhou, Nan; Cai, Xiang; Latief, Rashid (Frontiers in Environmental Science, 2022)
Environmental issues are getting greater attention now that experts and authorities are paying attention to global warming. The industrial segment is mostly to blame for these environmental hitches, according to past research. The industrial sector is actively addressing the issues brought on by climate change. This study's primary focus is on business environmental strategies in green innovation, which takes into account the company's goals for sustainable development. This study also takes into account the importance of corporate management (CEO, ownership concentration, and gender diversity) for green innovation. This study evaluated fact by natural resource theory, resource dependency theory, agency theory and Porter hypothesis. Results from practical generalized least squares and generalized moments approaches provide various conclusions. The findings of this study demonstrated that companies with business environmental strategies as, environmental regulation, proactive environmental plans, corporate social responsibility, and board sustainable committees were more likely to implement green innovation practices. Additionally, corporate management (CEO, ownership concentration, and gender diversity) supports businesses' efforts to innovate in the green sector. Importantly, our research showed that the importance of corporate management (CEO, ownership concentration, and gender diversity) in business environmental policies cannot be overstated (environmental regulations, proactive environmental strategies, corporate social responsibility, board sustainable committee, and green innovation). green innovation, as well. These findings significantly expand the scant amount of knowledge on corporate environmental initiatives and green innovation. In order to encourage green innovation for higher profitability while minimizing negative industrial consequences, this study also provides a number of suggestions and recommendations for stakeholders, including regulators, owners, and governments.